Agricultural exports from Russia to Asian countries: Analysis of prospects and trends - V. Moshchenko, Oksana (2020)
The recent recovery in Russian agriculture is due not only to the producers support from the State, but also to an increase in the production of foodstuffs substituting the imported ones. This was a result of negative foreign policy factors, and now further promising guidelines for Russian agriculture are expected to be developed by the government. The article is relevant due to the fact that the expansion of agricultural exports is a strategically important task for the entire Russian economy. The article analyzes the dynamics of agricultural production in Russia by farm categories over the past 19 years, as well as the production of main types of import-substituting foods for 2017-2018. The main agricultural exports to the Asian countries are identified and grouped. The current state and the possibility of a potential increase in exports of agricultural products by sectors of agro-industry have been studied. On the example of priority agro industries, ensuring the strategic expansion of exports to Asian countries, the current financial and economic state of the largest agro-industrial enterprises has been studied using special indicators of the SPARK system (system of professional analysis of markets and firms in Russia). The analysis showed that more than 90% of companies fall into the low-risk group by composite risk indicator, which is undoubtedly a positive development. This increases the likelihood of these entities stable development and the growth of their exports to Asian countries.